External Reserves and Macroeconomic Stability: Evidence from Sub-Saharan African Countries - Falmata Baba Abba; Yagana Alhaji Baba; Amina Ahmed Idris (Solo International Collaboration and Publication of Social Sciences and Humanities, 2024)
This study investigates the effect of foreign exchange reserves accumulation on macroeconomic stability proxied by inflation, unemployment, exports, and GDP for a sample of 49 Sub-Saharan African countries from 2009 to 2021 using a panel (longitudinal) fixed model. Findings from this study reveal that foreign exchange reserves have a significant negative effect on unemployment and inflation; however, it shows a significant positive effect on exports, while gross domestic product (GDP) shows no significant relationship with foreign exchange reserves. To improve the overall economy of the listed sub-Saharan countries, the paper, therefore, recommends that sub-Saharan African countries adopt a mixture of investment-friendly and unemployment reduction policies by reinvesting investible surplus into inflationary controllable and productivity-boosting policies that will stimulate economic growth rather than keeping this huge amount of resources redundant. The study adopted a qualitative research methodology where the study uses panel data, the data is secondary and is sourced from the World Bank Development Indicators.